Selective gating to vibrational modes through resonant X-ray scattering - Rafael C. Couto (Nature Portfolio, 2017)
Investigating dynamics of polyatomic molecules is difficult as their potential energy surfaces are multidimensional due to coupled degrees of freedom. Here the authors demonstrate a spatial selective gating technique to probe the different vibrational modes of water upon core-level excitation with X-rays.